Ciclo anual da precipitação e temperatura do ar em Conceição do Araguaia no sudeste do Pará: climatologia e tendências (1961-2011) - FERREIRA, Leonardo Bentivi (2019)
The Amazon, which is located between the Tropics of Cancer and Capricorn, has great influence on rainfall in the North, where, through the mechanism of global circulation, the energy released in the condensation process air is transported to other latitudes, providing a global thermal equilibrium. This paper presents an analysis on the observational aspects of the climatological annual cycle of precipitation and maximum and minimum temperature particularly in the municipality of Conceição do Araguaia in southeastern Pará, located within the arc of deforestation in the eastern Amazon. The historical average for 1961/2011 indicated that the rainy season occurs from November to April with an annual maximum reaching 270 mm in March and values of minimum temperature between 21 º C and 21.5 º C and maximum temperature between 31 º C and 32 º C. Moreover, characterized in June to September dry period with minimum annual only on July 6 mm, with a minimum temperature below 20 ° C and maximum temperature above 33 ° C. The quantitative trends of long-term, based on the differences between the mean of 20 years of 1961/1980 (former Amazon with more forest cover intact) and 1991/2011 (current deforested Amazon), showed that major climate changes consist of current regional warmer conditions (minimum temperature higher), with more intense rainy period (an increase of rain in May) and significantly more arid dry season (significant decrease of rainfall in June and July).We used monthly data of precipitation Project NETWORK OF CLIMATE AND FORECAST hydrometeorological PARÁ (RPCH) and the statistical technique of PERCENTILES, which enabled to quantify the intensity of a given rainfall event by bands or categories (XAVIER, 199).